The Resting‐State Activities of the Angular Gyrus and the Micturition Desire‐Awakening Function in Children With and Without Enuresis - Xindi Lin; Shaogen Zhong; Mengxing Wang; Yi Mao; Yuhan Wu; Jiayi Lu; Wei Zhong; Di Wu; Jun Ma (Brain and Behavior)
ABSTRACT Background Micturition desire‐awakening (MDA) function plays a pivotal role in the development of primary nocturnal enuresis (PNE); however, its neural correlates remain largely unexplored. Consequently, this study aimed to identify specific brain regional activities associated with MDA function. Methods Neuroimaging data were collected from 173 children with varying MDA functional grade scores at the Department of Developmental and Behavioral Pediatrics, Shanghai Children's Medical Center, from July 2018 to November 2022. Resting‐state images were analyzed using whole‐brain correlation techniques and AlphaSim correction to identify brain regional activities and resting‐state functional connectivity (RSFC) associated with MDA functional grade scores. Results Whole‐brain correlation analysis demonstrated that the fractional amplitude of low‐frequency fluctuations in the right angular gyrus (AG) exhibited a negative correlation with MDA functional grade scores (rs = −0.336, p < 0.001), indicating reduced neural activity in this region with MDA dysfunction. Conversely, RSFC between the right middle frontal gyrus and the right AG was positively correlated with MDA functional grade scores (rs = 0.274, p < 0.001), suggesting increased connectivity in these areas associated with worse MDA functionality. Conclusion These findings provide preliminary insights into the neural underpinnings of MDA functionality.